Clinical Effectiveness and Tolerability of Apremilast in Moderate-to-Severe Plaque Psoriasis: Insights from Real-World Practice Moderate-to-Severe Plaque Psoriasis: Insights from Real-World Practice - Meltem Turkmen; Musa Harun Göçmen; Emre Sarıkaya; Selcen Kundak; Ayris Öztürk; Elif Günay (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Apremilast is an oral phosphodiesterase-4 inhibitor approved for the treatment of moderate-to-severe plaque psoriasis. Although its efficacy and safety have been demonstrated in randomized controlled trials, real-world data remain limited. This study aimed to evaluate the real-world effectiveness and safety of apremilast in patients with moderate-to-severe plaque psoriasis. This retrospective observational study included 50 adult patients with moderate-to-severe plaque psoriasis treated with apremilast. Demographic and clinical characteristics were recorded. Disease severity was assessed using the Psoriasis Area and Severity Index (PASI) at baseline and at weeks 2, 4, and 8. Treatment response was evaluated based on PASI improvement rates (PASI 75 and PASI 100). Adverse events were documented. The study population consisted of 29 females and 21 males, with a mean age of 43 ± 5.5 years and a mean disease duration of 12 ± 3.1 years. Thirty-four patients were biologic-naïve and 16 were biologic-experienced. Mean PASI score decreased from 18.3 at baseline to 12.3 at week 2, 10.8 at week 4, and 7.2 at week 8. At week 4, PASI 75 and PASI 100 responses were achieved by 42% and 18% of patients, respectively, increasing to 58% and 34% by week 8. The most common adverse events were nausea (28%), headache (18%), and diarrhea (16%), most of which were mild and transient. Apremilast demonstrated rapid and clinically meaningful improvement in disease severity with a favorable safety profile in patients with moderate-to-severe plaque psoriasis. These real-world findings support apremilast as an effective and well-tolerated systemic treatment option in routine clinical practice.